VD_FINDINFO 117/2010/PMR vom 10. September 2010 - VD Tribunal cantonal (2010)
DÉCISION INCIDENTE, COMPÉTENCE RATIONE LOCI, TESTAMENT, SUCCESSION, DROIT INTERNATIONAL PRIVÉ, ÉLECTION DE DROIT, PROROGATION DE FOR | 147 CPC, 150 al. 2 CPC, 19 CPC, 58 al. 1 CPC, 58 al. 2 CPC, 59 al. 1 CPC, 90 al. 1 CPC, 91 let. c CPC, 92 al. 1 CPC, 86 al. 1 LDIP